Tool for Drought Monitoring in the Danube Region: – Methods and Preliminary Developments - Bucur, Andreea; Gregorič, Gregor; Grlj, Aleš; Kokalj, Žiga; Sušnik, Andreja (Journal of Environmental Geography, 2018)
Drought is a naturally recurring phenomenon of the climate system that affects virtually all regions of the world. During the past decades extreme droughts with extensive negative effects on ecosystems became evident also in the Danube region. At the moment regional capacity to monitor drought is still very diverse and not synchronised among different countries. In this is paper, we present a recently developed drought monitoring tool – the Drought User Service (DUS) for the Danube region using remote-sensing products which aims at offering a more accurate and in near-real-time monitoring via different drought indices. The DUS was created as the monitoring tool of the risk-based paradigm, which seeks to give information in near real-time about the location and severity of droughts throughout the Danube region. Satellite remote sensing products meet the requirements for operational monitoring because they are able to offer continuous and consistent measurements of variables, which can be used to assess the severity, spatial extent and impacts of drought. In the DUS three different variables – vegetation, soil moisture and precipitation – are monitored with earth observation products. The condition of vegetation and soil moisture is tracked with two simple indicators computed as long-term anomalies of the NDVI and SWI products made available through EU’s Copernicus Global Land Service. The importance of DUS and of the developed methods for faster detection of drought onset as useful foundation for establishing a better pro-active drought management in order to mitigate the negative effects of drought in the region is discussed.